2005
DOI: 10.1111/j.1466-822x.2005.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Energy flux, body size and density in relation to bird species richness along an elevational gradient in Taiwan

Abstract: Aim To examine the species richness of breeding birds along a local elevational gradient and to test the following assumptions of the energy limitation hypothesis:(1) the energy flux through birds is positively correlated with above-ground net primary productivity, (2) bird density is positively correlated with total energy flux, and (3) bird species richness is positively correlated with bird density.Location An elevational gradient from 1400 to 3700 m on Mt. Yushan, the highest mountain in Taiwan (23 ° 28 ′ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 51 publications
(78 reference statements)
2
33
0
1
Order By: Relevance
“…The pattern of the avian community of the present study varies from that reported by many previous studies conducted on bird species richness along altitudinal gradients mostly in temperate regions. Most such studies have found the highest species richness at low elevation such as in rain forest of eastern Andes Peru (Terborgh 1971;Terborgh & Weske 1975) or mid elevation such as in Peruvian Andes (Rahbek 1995(Rahbek , 2005, Madagascan rain forest (Colwell & Lees 2000), Bolwian Andes South American Forest (Kessler et al 2001), Columbian Andes forest (Kattan & Franco 2004), urban/subtropical to subarctic forest in Taiwan (Lee et al 2004;Ding et al 2005). In the present study the higher BSD and BSR observed in high altitude areas may be connected to the higher plant diversity.…”
Section: Discussionmentioning
confidence: 49%
“…The pattern of the avian community of the present study varies from that reported by many previous studies conducted on bird species richness along altitudinal gradients mostly in temperate regions. Most such studies have found the highest species richness at low elevation such as in rain forest of eastern Andes Peru (Terborgh 1971;Terborgh & Weske 1975) or mid elevation such as in Peruvian Andes (Rahbek 1995(Rahbek , 2005, Madagascan rain forest (Colwell & Lees 2000), Bolwian Andes South American Forest (Kessler et al 2001), Columbian Andes forest (Kattan & Franco 2004), urban/subtropical to subarctic forest in Taiwan (Lee et al 2004;Ding et al 2005). In the present study the higher BSD and BSR observed in high altitude areas may be connected to the higher plant diversity.…”
Section: Discussionmentioning
confidence: 49%
“…On Taiwan it is a common breeder in the coniferous forests of the central mountain ridges at altitudes from roughly 2,000 to 3,700 m asl. The species is fairly common in stands dominated by Abies kawakamii, Tsuga formosana, and Picea morrisonicola but also inhabits coniferous and broad-leaved mixed forests, and only during the winter season do populations move vertically to lower elevations (Ding et al 1997(Ding et al , 2005; Shiu and Lee 2003; Lei and Taichun 2004;del Hoyo et al 2006). Currently the species status of the Taiwan population is not seriously in doubt and there has never been a real debate on its presumed close phylogenetic relationships to Regulus ignicapillus (Voous 1962;Desfayes 1965; Mayr and Short 1970;Eck 1996;Glutz von Blotzheim and Bauer 1991).…”
Section: Introductionmentioning
confidence: 97%
“…Almost all of our species richness and hotspot analyses revealed that mountainous regions of Taiwan hold most of Taiwan's avian biodiversity. Previous studies showed a humpshaped relationship between avian species richness and Taiwan's elevation gradient, meaning that the highest species richness was found in mid-elevation forests (Koh and Lee 2003;Shiu and Lee 2003;Hsu et al 2004;Lee et al 2004;Ding et al 2005;Koh et al 2006b), which is unlike the species richness pattern found on Hainan Island, China in the northwestern South China Sea Columns 3 to 9 show how many of the grid cells of column 2 fell within the various protected area categories, followed by the percentages in brackets (e.g., for hotspot criterion 4, eight of a total of 47 grid cells (17.0%) were inside national parks). Note that the highest protection level (i.e., national parks) plus nature reserves, forest reserves, and wildlife refuges was defined as medium-to-high protection and that the addition of major wildlife habitats was then defined as low-to-high protection (see the 'Methods' section for details).…”
Section: Discussionmentioning
confidence: 99%